Six Gynecological Cancer Patients Infected With SARS-CoV-2 After Surgery or Radio-/Chemo-Therapy Treatment: Case Series - Liu, Chen; Huang, Yuhan; Qin, Tianyu; Guo, Ensong; Wu, Peng; Sun, Chaoyang; Chen, Gang (Frontiers in Oncology, 2020)
Objective: Recently, the number of gynecological cancer patients infected with SARS-CoV-2 has been increasing. So, this study was committed to researching the impact of gynecological cancer treatment on the Coronavirus Disease 2019 (COVID-19), which was of great significance for the treatment of gynecological cancer patients during the outbreak of COVID-19. Methods: We retrospectively analyzed the diagnosis and treatment of six gynecological cancer patients infected with SARS-CoV-2 in Tongji Hospital in Wuhan from 30th January to 25th March 2020. To guide the treatment of gynecological cancer patients better during the epidemic, we summarized the case characteristics, auxiliary examination, treatment plan, and outcome of these six patients. Results: After radio-/chemo-therapy or surgery of gynecological cancer patients, we observed a high rate of nosocomial SARS-CoV-2 infection. Also, some gynecological cancer patients had COVID-19-related atypical symptoms due to the influence of cancer treatment, which resulted in delayed diagnosis time. Furthermore, as for treatments of these cases, in addition to symptomatic antiviral treatment, immune boosters, and reagents that raised white blood cells were applied. At present, all cases in this study had been discharged from the hospital with a good prognosis. Conclusion: After radio-/chemo-therapy treatment or surgery, gynecological cancer patients had a high rate of nosocomial infection. Besides, the history of cancer treatment made the diagnosis of COVID-19 difficulty, which also affected the treatment of COVID-19. Therefore, we put forward the corresponding therapy suggestions for gynecological cancer patients during the outbreak of COVID-19.